لدى طلبة دبلوم التأهيل التربوي وممارساتهم التدريسية في جامعة دمشق (VARK) العلاقة بين أنماط التعلم المفضلة وفق نموذج فارك: Preferred Learning Styles Based on the VARK Model among Diploma of Educational Qualification Students and Their Teaching Practices at Damascus University - Ebtisam Mohmed Fares (LISANIA: Journal of Arabic Education and Literature, 2026)
This study explored the relationship between preferred learning styles based on the VARK model and teaching practices among Diploma of Educational Qualification students at Damascus University using a descriptive-analytical design. A total of 120 students participated in the study, and data were collected through a VARK-based learning styles questionnaire and a teaching practices scale to identify students’ dominant learning preferences and instructional tendencies. The findings indicated that the kinesthetic learning style was the most dominant among students (M = 4.75), while teaching practices tended to emphasize auditory-verbal practices, with an overall moderate level (M = 3.27). The results also revealed no statistically significant relationship between learning styles and teaching practices (χ² = 6.829, p > 0.05), suggesting that preferred learning styles may not directly influence classroom teaching practices. Furthermore, multiple linear regression analysis showed that learning styles were not significant predictors of teaching practices (F = 0.682, p > 0.05). In addition, no statistically significant differences were found in either learning styles or teaching practices based on gender, college type, or years of experience, indicating relatively similar instructional tendencies among participants regardless of demographic background. Based on these findings, the study recommends enhancing teachers’ use of diverse instructional strategies that accommodate various learning styles and developing effective guidelines to improve teaching practices, while also emphasizing the importance of learner-centered approaches in teacher preparation programs.